1995
DOI: 10.1091/mbc.6.11.1459
|View full text |Cite
|
Sign up to set email alerts
|

Membrane protein retrieval from the Golgi apparatus to the endoplasmic reticulum (ER): characterization of the RER1 gene product as a component involved in ER localization of Sec12p.

Abstract: Yeast Sec12p, a type II transmembrane glycoprotein, is required for formation of transport vesicles from the endoplasmic reticulum (ER). Biochemical and morphological analyses have suggested that Sec12p is localized to the ER by two mechanisms: static retention in the ER and dynamic retrieval from the early region of the Golgi apparatus. The rer1 mutant we isolated in a previous study mislocalizes the authentic Sec12p to the later compartments of the Golgi. To understand the role of RER1 on Sec12p localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 56 publications
5
101
0
Order By: Relevance
“…The first of these described was the HDEL receptor, Erd2, described above, where the lumenal domain likely provides ligand-binding function (Scheel and Pelham 1998), with changing pH conditions likely driving binding and release in the appropriate compartments (Wilson et al 1993). Another well-described cargo adaptor is the membrane protein Rer1 (Nishikawa and Nakano 1993;Sato et al 1995), which is important for the efficient retrieval, and thus steady-state ER localization, of some ER resident proteins, including the COPII GEF, Sec12, and the translocon components, Sec63 and Sec71 (Sato et al 1997). The reason these proteins would require an escort back to the ER rather than employing their own retrieval motifs is unclear, but Rer1 seems to bind these clients within their transmembrane domains, via polar residues embedded within the hydrophobic environment (Sato et al 1996(Sato et al , 2001).…”
Section: Composition and Structure Of The Copi Coatmentioning
confidence: 99%
“…The first of these described was the HDEL receptor, Erd2, described above, where the lumenal domain likely provides ligand-binding function (Scheel and Pelham 1998), with changing pH conditions likely driving binding and release in the appropriate compartments (Wilson et al 1993). Another well-described cargo adaptor is the membrane protein Rer1 (Nishikawa and Nakano 1993;Sato et al 1995), which is important for the efficient retrieval, and thus steady-state ER localization, of some ER resident proteins, including the COPII GEF, Sec12, and the translocon components, Sec63 and Sec71 (Sato et al 1997). The reason these proteins would require an escort back to the ER rather than employing their own retrieval motifs is unclear, but Rer1 seems to bind these clients within their transmembrane domains, via polar residues embedded within the hydrophobic environment (Sato et al 1996(Sato et al , 2001).…”
Section: Composition and Structure Of The Copi Coatmentioning
confidence: 99%
“…One of the major efforts in our laboratory then was to understand the role of yeast Rer1p, a membrane protein in the cis-Golgi, in vesicle recycling between the ER and the Golgi (Nishikawa and Nakano, 1993;Sato et al, 1995;Nakano, 2002). We had several lines of evidence indicating that Rer1p is required for retrieval of a subset of ER membrane proteins from the Golgi to the ER (Sato et al, 1996;Sato et al, 1997).…”
Section: Dynamics Of Yeast Golgi Apparatusmentioning
confidence: 99%
“…This construct was confirmed for its ability to complement arf1 null strains. pSKY5RER1-0 is a singlecopy plasmid expressing a green fluorescent protein (GFP)-Rer1p protein, in which EGFP1 (CLONTECH, Palo Alto, CA) is fused to the N terminus of Rer1p (Sato et al, 1995), under control of the TDH3 promoter. Saccharomyces cerevisiae strains used in this study are listed in Table 1.…”
Section: Strains Plasmids and Mediamentioning
confidence: 99%
“…Ken Sato, one of the authors of this paper, has been working on Rer1p, a membrane protein in the cisGolgi. Rer1p is required for the correct localization of a set of ER membrane proteins such as Sec12p, Sec63p, and Sec71p by a retrieval mechanism utilizing COPI vesicles (Nishikawa and Nakano, 1993;Sato et al, 1995Sato et al, , 1997. To observe the dynamic behavior of Rer1p in living yeast cells, Sato constructed a fusion protein between Rer1p and the green fluorescence protein (GFP-Rer1p) and found that its localization is determined by the equilibrium of very active membrane recycling (Sato, Sato, and Nakano, unpublished data).…”
Section: Localization Of Gfp-rer1pmentioning
confidence: 99%